أثر منطقة التجارة الحرة العربية الكبرى في القطاع الزراعي في الساحل السوري - محمود حبيب (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث انعكاسات منطقة التجارة الحرة العربية الكبرى على القطاع الزراعي في الساحل السوري, بداية يلقي البحث الضوء على أهم بنود الاتفاقية وتشريعاتها, ثم ينتقل للخوض في تأثيراتها المحتملة على القطاع الزراعي في الساحل السوري مقدما دراسة عملية رقمية لحالة من تطبيق الدورة الزراعية المشتركة, وقياس تأثيراتها وصولا إلى تحديد آثارها بدقة في القطاع الزراعي في الساحل السوري. في النهاية يقدم البحث خطة من عدة نقاط من أجل الاستفادة من تطبيق اتفاقية التجارة على القطاع الزراعي في الساحل السوري انطلاقا من الخصائص النسبية للقطاع الزراعي في الساحل السوري. The search tackles the effects of the large Arab free trade on the farming sector in the Syrian coast. First, it throws light on the most important items and legislations of the agreement. Then, it moves to analyze its possible effects on the farming sector in Syrian Coast. The paper introduces numerous and practical studies for several cases using mixed farming agenda in order to identify the effects and reach the correct consequences on farming sector. At the end, the search provides a plan of various points in order to benefit from the application of trade agreement on farming sector in Syrian Coast, depending on characteristics for some agriculture at Syrian Coast.